Culture as Soft Power Bridging Cultural Relations, Intellectual Cooperation, and Cultural Diplomacy - Sanz, Diana Roig; Carbó-Catalan, Elisabet (De Gruyter, 2022)
Including a thorough literature review and a number of case studies referred to cultural institutions and organisations, this book sheds light on different usages of culture as a source of soft power. Through an innovative and interdisciplinary approach, it addresses issues tackled in international cultural relations, intellectual history, comparative literature, sociology of literature and global literary studies.